The settlement of Norabats - Devejyan, Seda; Davtyan, Ruben (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The Kura-Araxes settlement of Norabats situated in Ararat valley is characterized by its mostly circular mud brick constructions. South to them, seven round pits with 1-1.5 m in diameter were excavated. They show regularities in regard to their form and artefacts found there. After comprehensive description and discussion, we argue that these features were of economical character. Other characteristics of the site were braided baskets, still containing remains of sheep or goat dung. The latter was used probably as fertilizer in agricultural works or as fuel.